Red cell distribution width as a prognostic marker in diabetes; a pilot cross-sectional study - Saeed Shirali; Sara Bahadoram; Seyed Mohamad Kazem Nourbakhsh; Mohammad Bahadoram; Ali Asghar Valipour; Fatemeh Javanmardi (Society of Diabetic Nephropathy Prevention, 2019)
Introduction:Red cell distribution width (RDW) is one of the important factors in anisocytosis which is related to impairment of erythropoiesis and degradation of erythrocytes. Objectives: The aim of this study was to evaluate the use of RDW as a prognostic marker in diabetic patients. Patients and Methods: This cross-sectional study was conducted on 144 individuals who referred to laboratories in Khuzestan. Of all, 69 persons were diabetic patients and 75 were non-diabetic. Results: The mean fasting blood sugar (FBS) and RDW coefficient of variation (RDW-CV), were 85.20 ± 9.12 mg/dL and 13.26 ± 0.69% respectively, in the non-diabetic group, and 238.65 ± 70.54 mg/dL and 13.50 ± 0.74% respectively, in the diabetic group. In this study, a significant difference of mean FBS (P <0.001) and mean RDW (P=0.04) between groups were detected. Conclusion: In our study, a significant relationship between changes in RDW and changes in blood sugar in diabetic patients was detected. Studying RDW in diabetes delineated higher RDW values than in healthy population. Therefore, it can be recommended to apply serum RDW as a prognostic marker for diabetes. However additional studies on this subject are necessary